PENGARUH EWOM, KUALITAS ARGUMEN DAN KREDIBILITAS SUMBER DI MEDIA KASKUS TERHADAPAT MINAT PEMBELIAN SMARTPHONE ANDROID SERIES Study kasus (Samsung, Sony, Oppo dan Lenovo) - Budiarto B11110064, Eko Setiyo (Jurnal Manajemen Update, 2015)
This study aimed to analyze the influence of electronic word of mouth (e-WOM), the quality of the arguments, and the credibility of sources in media buying interest Kaskus against android smartphone series on Kaskus Region media members in West Kalimantan (RKB) who has made a purchase android smartphone series (Samsung, Oppo, Sony and Lenovo) through a communication made in the media Kaskus. This study using purposive sampling method, which have been as many as 100. The analysis technique used is to do a T test and F test using SPSS 15.0 veri. Data processing of test results showed that the T of each variable E-WOM, Quality argument, and the credibility of the source of the interest in the purchase of android smartphone series in the media Kaskus on Kaksus member RKB only argument Quality variable (X2) that there is no influence positive relationship Interests significantly to Buy (Y) mediated Android Smartphone Kaskus RKB because tcount (.831) smaller than the value ttable (1984). Through the coefficient of determination (R2) of the F test results in all the variables studied only has the effect of 23.5% against the interest Buy, then there is still 76.5% of other factors not examined in this study that may affect the buying interest in the media Kaskus RKB. Â  Keywords: electronic word of mouth (e-WOM), quality of the arguments, and the credibility of the source, and interest in purchasing